Clonal hematopoiesis-associated motoric deficits caused by monocyte-derived microglia accumulating in aging mice - Kim, Jung-Seok; Trzebanski, Sébastien; Shin, Sun-Hye; Schori, Lior; Frumer Friedman, Gal Ronit; Ilani, Noa Chapal; Kadam, Aditee; Vicario, Rocio; Aust, Oliver; Bugaeva, Polina; Piatek, Sylwia; Ismajli, Laura Kate; et al. (Cell reports, 2025)
Microglia are parenchymal brain macrophages that are established during embryogenesis and form a self-containing cellular compartment that resists seeding with cells derived from adult definitive hematopoiesis. We report that monocyte-derived macrophages (MoMΦs) accumulate in the brain of aging mice with distinct topologies, including the nigrostriatum and medulla but not the frontal cortex. Parenchymal MoMΦs adopt bona fide microglia morphology and expression profiles. Due to their hematopoietic stem cell (HSC) derivation, monocyte-derived microglia (MoMg) are unlike yolk-sac-derived cells, targets of clonal hematopoiesis (CH). Indeed, using a chimeric transfer model, we show that the hematopoietic expression of DNMT3AR882H, a prominent human CH variant, renders MoMg pathogenic and promotes motor deficits resembling atypical Parkinsonian disorders. Collectively, we establish that MoMg progressively seed the brain of healthy aging mice, accumulate in selected areas, and, when carrying a somatic mutation associated with CH, can cause brain pathology.